Agriculture in Jamaica : 1991-1995 and beyond - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2017)
The information and analysis are based on statistics and descriptive information extracted from various national sources, as well as from reports generated by regional and international counterpart institutions. It is anticipated that the information will be useful, not only to individuals and institutions working in agricultural development will be useful, not other parties interested in information on the agricultural sector in general.